PENGARUH PRODUK, PERSEPSI HARGA, PROMOSI DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH DI SOLO RAYA - Kusnul Khotimah; Andri Nurtantiono (Creative Research Management Journal, 2021)
The purpose of this study was to determine the effect of products, price perceptions, promotions and lifestyle onWardah product purchasing decisions in Solo Raya. The population in this study is an unlimited population because the population is unknown. The method of determining the sample is purposive sampling. The number of samples obtained by 97 respondents. Using multiple linear regression analysis techniques. Collecting data in the form of a questionnaire and the measurement scale is a Likert scale. The results of the research are the product has no partial or individual effect on the purchasing decision of Wardah products in Solo Raya, Price Perception has no partial or individual effect on the purchasing decision of Wardah products in Solo Raya, Promotion has no partial or individual effect on the purchasing decision of Wardah products in Solo Raya, Gaya Life has a partial or individual effect on the Purchase Decision of Wardah products in Solo Raya. Product, Price Perception, Promotion, Lifestyle have a simultaneous effect on the Purchase Decision of Wardah products in Solo Raya